Precuneus-Dominant Degeneration of Parietal Lobe Is at Risk of Epilepsy in Mild Alzheimer's Disease - Horvath, Andras; Kiss, Mate; Szucs, Anna; Kamondi, Anita (Frontiers in Neurology, 2019)
Introduction Alzheimer’s disease (AD) is the leading cause of cognitive decline. Epilepsy is a frequent comorbid condition of AD. While previous studies analysed the risk factors of AD-related epileptic seizures, we still lack biomarkers of epilepsy in mild AD cases. Purpose The aim of our study was to analyse the correlations between neuropsychology, cortical thickness and brain volumetric measurements in mild Alzheimer patients with concomitant epileptic seizures. Materials and methods We selected mild AD patients from our database for examining them with structural magnetic resonance imaging, 24-hour electroencephalography and detailed neuropsychology. We made the diagnosis of epilepsy based on epileptology data including neurophysiology. We retrospectively analysed the neuropsychology pattern, clinical and epidemiologic features, cortical thickness and volumetric values of mild AD patients with and without overt clinical seizures using covariance weighted general linear model. Results We found epileptic seizures in 26% of mild AD patients. Patients with seizures performed worse in visuo-spatial scores than patients without (p:0.003). Patients with seizures had smaller parietal thickness (p:0.018) being associated to reduced thickness of left (p:0.007) and right precunei (p:0.005). The visuo-spatial performance positively and strongly correlated with the thickness of the parietal lobe (r:0.67; p:0.002) and with the volume of the precuneus (r:0.612; p:0.005). Conclusion Epileptic seizures are common even in mild AD. We found that a prominent deficit in visuo-spatial skills is a red flag for epileptic seizures in the initial phase of Alzheimer’s disease indicating the early involvement of parietal lobe in the neurodegenerative process. Because our findings suggest that the degeneration of precuneus is a sensitive marker of seizures associated to mild AD, clinicians need to pay special attention to the pattern of atrophy shown by structural MRI. Our results confirm previous data suggesting that epileptic seizures might associate to a faster progressing type of AD with the early degeneration of posterior cortical areas.